Industrial Relations in Canadian Industries - Boivin, Jean (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Industrial Relations in Canadian Industries," edited by Richard P. Chaykowski and Anil Verma.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z